Communication of information about oral and oropharyngeal cancer: the quality of online resources. (11th February 2016) - Bánki, F.; Thomas, S.J.; Main, B.G.; Waylen, A.E.
Abstract: Aim: To critically appraise the content, quality and readability of websites that provide online information about oral and oropharyngeal cancer and are accessible by people diagnosed with that condition. Material and methods: Three popular search engines were used to find websites providing information about oral and oropharyngeal cancer, and all links that presented on the first page of the search were analysed. Included sites were assessed for content (intended audience, and evidence of quality assurance). The validated DISCERN tool was used to assess the quality of sites. A readability score was calculated. Descriptive and inferential statistical analyses were performed. Results: A total of 162 web sites were examined. The majority (87%) were written for a clinical audience. Most (89%) did not display evidence of quality assurance. The median overall quality (DISCERN) score was 2.0, indicating potentially serious shortcomings. There was a correlation between the DISCERN scores and evidence of quality assurance certification, but this was not seen for readability. Conclusion: The quality of online information that may be accessed by people with oral and oropharyngeal cancer when seeking information online remains poor.